Enablers and barriers to the implementation of breast self-examination (BSE) education programmes among adolescent girls in Sub-Saharan Africa (SSA): an integrative systematic review protocol - Emmanuel Osei Bonsu; Isaac Yeboah Addo; Caleb Boadi; Benedictus Atsu Hlormenu; William Dormechele; Mercy Oseiwah Adams; Bright Boatey Bossman; Stephen Kwakye Addo (BMJ Open)
Background Breast cancer is emerging as a leading cause of mortality among women and adolescent girls in Sub-Saharan Africa (SSA). However, there is a lack of clarity on the enablers and barriers associated with the implementation of preventive strategies, such as breast self-examination (BSE), particularly among adolescent girls.Objective This paper presents a protocol for conducting a systematic review aiming to synthesise studies on the enablers and barriers to implementing BSE education programmes among adolescent girls in SSA.Methods and analysis The systematic review will be conducted from December 2024 to August 2025, following the predefined methodological framework outlined in the PRISMA guidelines. To gather relevant studies, a comprehensive search will be conducted across four main online databases, namely PubMed, Scopus, Cochrane Library and EMBASE, along with other relevant grey literature sources, such as Google Scholar, to identify pertinent literature on this topic. The screening process will involve an initial review of titles and abstracts to quickly identify relevant studies, followed by a thorough assessment of the full-text versions of selected studies. Two reviewers, working independently, will extract data and evaluate the risk of bias in the included studies using either the Joana Briggs Institute’s Critical Appraisal tool or Cochrane’s Risk of Bias tool V.2 (RoB 2). The focus of the included studies will be on BSE among adolescents aged 10 to 19 years of age. Depending on the results of the literature search and the characteristics of the findings in the selected studies, we will conduct a meta-analysis if possible. Alternatively, a narrative synthesis will be conducted. The review will provide empirical evidence to inform health promoters and policymakers in advocating for BSE, particularly, among adolescent girls in SSA, with the ultimate goal of mitigating the risk of breast cancer.Ethics and dissemination Since this study is based on the analysis of already published research articles, ethical approval is not required. The results will be disseminated through peer-reviewed academic publications and presentations, informing further research and practice regarding BSE education programmes.